2021
DOI: 10.1186/s12939-021-01530-2
|View full text |Cite
|
Sign up to set email alerts
|

Family doctor contract services and health-related quality of life among patients with chronic diseases in rural China: what is the role of socioeconomic status?

Abstract: Purpose Few studies explored the relationship between the family doctor contract services (FDCS) and health-related quality of life (HRQOL) among patients with chronic diseases in rural China. This study aims to explore the relationship between the status of signing on FDCS and HRQOL among patients with chronic diseases and examine whether there are differences in the relationship between different socioeconomic status (SES). Methods A total of 1,2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 28 publications
(22 reference statements)
0
10
0
Order By: Relevance
“…Our results also found that patients who contracted with a family physician had more frequent outpatient visits and longer inpatient stays. A plausible explanation might be that contracting with a family physician is associated with higher income levels, which could enhance patient disease awareness and treatment compliance ( 37 ). However, family physicians serve as the gatekeepers to health care, aiming to prevent chronic diseases by intervening in disease-related lifestyle behaviors in addition to delivering primary health care services that can efficiently lower the hospitalization and mortality of patients and mitigate the burden of chronic disease in China ( 37 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our results also found that patients who contracted with a family physician had more frequent outpatient visits and longer inpatient stays. A plausible explanation might be that contracting with a family physician is associated with higher income levels, which could enhance patient disease awareness and treatment compliance ( 37 ). However, family physicians serve as the gatekeepers to health care, aiming to prevent chronic diseases by intervening in disease-related lifestyle behaviors in addition to delivering primary health care services that can efficiently lower the hospitalization and mortality of patients and mitigate the burden of chronic disease in China ( 37 ).…”
Section: Discussionmentioning
confidence: 99%
“…A plausible explanation might be that contracting with a family physician is associated with higher income levels, which could enhance patient disease awareness and treatment compliance ( 37 ). However, family physicians serve as the gatekeepers to health care, aiming to prevent chronic diseases by intervening in disease-related lifestyle behaviors in addition to delivering primary health care services that can efficiently lower the hospitalization and mortality of patients and mitigate the burden of chronic disease in China ( 37 ). The effect of family physician contracting on the outpatient and inpatient services that were utilized by cancer patients remains for consideration.…”
Section: Discussionmentioning
confidence: 99%
“…in Heilongjiang province suggested that there was a gap between actual and desired workplace characteristics, which had a negative influence on workers’ job satisfaction [ 42 ]. The popular researches about family doctors focused on the effect and challenge of family doctor contract services [ 43 48 ], chronic disease management to contract with family [ 50 ] and assessment of Chinese family physicians’ service competences [ 51 ]. Up to this point, these studies about job satisfaction and family doctors have been explored, however, these studies usually discussed other medical occupations or the effect of implementation family doctor policies, lacking of the overall occupational perception survey among family doctors at Community health centres.…”
Section: Introductionmentioning
confidence: 99%
“…[6][7][8] The contract service is a voluntary bi-direction free health management supplementary service supported by the central government in China. 5,9,10 The service has been regarded as a critical strategy to provide continuous primary care and improve health awareness of the vulnerable populations, such as senior citizens, pregnant women and patients with non-communicate chronic diseases. 11 Many empirical studies have reported the positive feedback on contract service with cross-sectional data, especially for chronic disease patients.…”
Section: Introductionmentioning
confidence: 99%
“…11 Many empirical studies have reported the positive feedback on contract service with cross-sectional data, especially for chronic disease patients. 4,10,[12][13][14] Compared with other types of regular primary care and regular primary care doctors, family doctor contract service (FDCS) improved the health outcome of community residents, and households reported to receive follow-up on treatments more efficiently. 14 It was also proved to be a cost-effective intervention for chronic disease patients.…”
Section: Introductionmentioning
confidence: 99%